Respeaking certification Bringing together training, research and practice - Romero-Fresco, Pablo; Melchor-Couto, Sabela; Dawson, Hayley; Moores, Zoe; Pedregosa, Inma (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2020)
Research and training in respeaking are still lagging behind professional practice. One of the consequences of this lack of training opportunities is the UK government’s refusal, in 2016, to use the Disabled Students’ Allowances (DSA) to provide for respoken subtitles, arguing that respeaking was not a qualified profession. In order to tackle this issue, the Galician Observatory for Media Accessibility set up LiRICS, the Live Respeaking International Certification Standard, which aims to set and maintain high international standards in the respeaking profession. In 2019, after assessing the online certification process proposed by LiRICS, the Department of Education in the UK concluded that it meets their requirements and that LiRICS-certified respeakers are eligible for Disabled Students’ Allowances funding. This article outlines, first, the current provision of respeaking training around the world and the assessments of live subtitling quality carried out to date, both of which inform the LiRICS online certification process presented here. The focus is then placed on the actual certification process, including a description of the tests, the platform used and the quality assurance process. This is followed by an analysis of the respeakers’ performance, which has been shown to be in line with current professional standards.